Case report: Immoderate perfume use leading to non-keratinising sinonasal squamous cell carcinoma with bone and lung metastases - Zia, Shamail; Shamail, Farozaan; Zia, Fazail; Uddin, Naeem; Zia, Vardah; Naeem, Shamsa (Journal of the Pakistan Medical Association, 2026)
Squamous cell carcinoma (SCC) of the sinonasal tract (SNSCC) is a cancerous epithelial tumour which originates from the epithelium surface lining the nasal cavity and paranasal sinuses and shows squamous differentiation. Here, we report the case of a patient who had the habit of soaking cotton cloth at night with perfume and spreading it over his face and sleeping for around eight hours in this position. The patient had been doing this for 30 years without any gap and presented with complaints of nose bleed and difficulty in breathing since three to four months. Upon scanning of the face, a polypoidal lesion was seen in the left nasal cavity causing partial obstruction of the nasal cavity. Biopsy of the nasal mass confirmed the presence of neoplastic lesions positive for cytokeratin 5/6 diagnosed as non-keratinising SCC. Upon further evaluation of symptoms, metastases in bones and lungs were also confirmed. Keywords: Nasal cavity, Paranasal sinuses, Perfume, Carcinoma, Keratin-5.